PEMBUATAN DAN KARAKTERISASI NANOKOMPOSIT MFe2O4 DAN MFe2O4-SiO2 (M = Cu, Ni) - -, Rahmayeni; Arief, Syukri; Stiadi, Yeni; Oktavani, Herlin (Jurnal Riset Kimia, 2010)
Nanocomposites of MFe2O4 and MFe2O4-SiO2 (M= Cu, Ni) were prepared by complexation and complexs polymerization methods using citric acid as complexing agent, tetraethylorthosilicate (TEOS), metal (Cu, Ni) nitrate and iron chloride as precursors. FT-IR spectroscopy was used to analysis the complexation and polymerization process. The decomposition of material was investigated by TG-DTA. Microstructure characterization was carried out by XRD and SEM. Peaks in XRD pattern indicate that the nanocomposites products consist of copper iron oxide (CuFe2O4) and (NiFe2O4) crystals, copper iron oxide crystal distributed in silica (CuFe2O4-SiO2) and nickel iron oxide crystal distributed in silica (NiFe2O4-SiO2). SEM images of CuFe2O4 and NiFe2O4 show that the composites have porous and spherical texture. The surface texture of CuFe2O4-SiO2 composite is triangel like and has porous but NiFe2O4-SiO2 is not regulated texture and has porous.  Keywords: MFe2O4, MFe2O4/SiO2, citric acid and complexs polymerization method